Penerapan Proses Sistem Pengendalian Manajemen Terhadap Perencanaan dan Penganggaran: (Studi Kasus Dinas Perindustrian dan Perdagangan Sumatera Utara Bidang Perdagangan dalam Negeri) - Dian Novitri; Budi Dharma (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The aim of this research is to determine the implementation of the process management system in planning and implementing budgets at the Ministry of Industry and Trade, North Sumatra Province. The research method used is descriptive qualitative, or a comprehensive problem solving procedure, which presents information obtained from interviews, literature reviews and field observations, which is then analyzed and interpreted through conclusions. Research Results In general, the management control system process is said to be successful if management is able to ensure that the company receives the necessary resources and is able to use them effectively and efficiently. In other words, the process can be said to be successful if the plans prepared by management can actually be implemented and the existing monitoring system can correct deviations that arise in time. Therefore, it is necessary to pay attention to the characteristics and stages of the system itself. In this case, it can be said that the development of the entire management control system process is expected to occur when responsibility is concentrated in easily monitored organizational units (e.g. departments, subdivisions, etc.) and with an effective and functional reporting system. can run well.